Analisis Risiko Ergonomi pada Pekerjaan Mengangkat Barang Menggunakan Metode Niosh Lifting Equation di Gudang PT. XYZ - Maghfur, Abdullah; Hidayat, Ade Nurul; Widya, Adi Rusdi (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This study aims to analyze ergonomic risk in manual lifting activities at the food storage warehouse of PT XYZ, located in Cikarang Barat, using the NIOSH Lifting Equation method. A total of 20 workers were observed, with ergonomic variables measured such as load weight, lifting frequency, lifting distance, and body posture. The results showed that the average initial Lifting Index (LI) was 2.328, significantly exceeding the safe threshold (LI ≤ 1), indicating a high risk of musculoskeletal disorders. After an intervention using a team lifting system, the average LI decreased to 1.207. Although not yet fully within the safe zone, this method effectively reduced ergonomic risk. Recommendations include ergonomic training, use of lifting aids, and broader implementation of team lifting. This study employs a descriptive quantitative approach.